Impact of nonabsorbing anthropogenic aerosols on clear-sky atmospheric absorption - Stier, P; Seinfeld, J; Kinne, S; Feichter, J; Boucher, O (2006)
Absorption of solar radiation by atmospheric aerosol has become recognized as important in regional and global climate. Nonabsorbing, hydrophilic aerosols, such as sulfate, potentially affect atmospheric absorption in opposing ways: first, decreasing absorption through aging initially hydrophobic black carbon (BC) to a hydrophilic state, enhancing its removal by wet scavenging, and consequently decreasing BC lifetime and abundance, and second, increasing absorption through enhancement of the BC absorption efficiency by internal mixing as well as through increasing the amount of diffuse solar radiation in the atmosphere. On the basis of General Circulation Model studies with an embedded microphysical aerosol module we systematically demonstrate the significance of these mechanisms both on the global and regional scales. In remote transport regions, the first mechanism prevails, reducing atmospheric absorption, whereas in the vicinity of source regions, despite enhanced wet scavenging, absorption is enhanced owing to the prevalence of the second mechanisms. Our findings imply that the sulfur to BC emission ratio plays a key role in aerosol absorption. Copyright 2006 by the American Geophysical Union.